Strengthening teacher competence as professional educators through the implementation of student-centered learning - Nurhemah, Neng; Putri, Mas Fierna Janvierna Lusie (Universitas Jambi, Indonesia, 2025)
This research aimed to strengthen teacher competence as professional educators by implementing student-centered learning at SMA Negeri 3 Tangerang City. In an education that continues to develop, teachers are required not only as material deliverers but also as learning facilitators. This research used a qualitative approach with data collection techniques through observation, interviews, and documentation studies. Respondents consisted of 10 teachers and 35 students. The research results indicated that implementing student-centered learning can increase engagement and interaction in the learning process and develop critical thinking skills. Training and professional development have also been key factors in enhancing teacher competence. This research recommends that schools continue to develop ongoing training programs and implement innovative learning methods to create a conducive learning environment and support the achievement of national education goals.